IN THE DEVELOPMENT OF HYDROMORPHIC SOILS THE IMPORTANTCE OF GROWING OILY PLANTS - Musurmonov Abror Alisherovich; Choriyev Jahongir Olimjon o’g’li; Ubaydullayeva Shohista Hidoyatillo qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The properties of hydromorphic soils depend on the level of groundwater, the degree of mineralization, as well as the regime of continuous floods. Experiments have shown that oilseeds can be grown in hydromorphic soils. The example of a single peanut plant can be used to show growth and yield in different hydromorphic soils. This increases the area of irrigated land and expands the raw material base of food plants.